Culture and Constitutional Compliance - Jerg Gutmann; Anna Lewczuk-Czerwińska; Jacek Lewkowicz; Stefan Voigt (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Constitutions as the formal foundation of a country's legal and political system have important economic and political effects. Yet, we still know little about why constitutions set effective constraints on politicians in some societies, while being largely disregarded in others. Here, we ask if national culture matters for constitutional compliance. We study a cross-section of 115 countries, making use of novel indicators of constitutional compliance. We find that societies with a more individualistic population exhibit higher levels of compliance. These results are robust and extend to instrumental variable estimations. They imply a novel transmission channel from cultural traits to long-term economic development: individualistic national culture increases the credibility of constitutional self-commitments. Our analysis also supports the more general idea that the effects of formal institutions depend on the informal institutional environment in which they are embedded. Regarding religion, our results are consistent with past research that attributes the lack of development in the modern Muslim world to deficient institutional quality.
Keywords: H11; K1; K42; P48; Z10; Z12; Z18; 330; constitutional compliance; culture; individualism; Islam; long-term orientation; moral universalism; power distance; rule of law